Brain-Derived Neurotrophic Factor (BDNF) Preserves the Functional Integrity of Neural Networks in the β-Amyloidopathy Model in vitro - Mitroshina, Elena V.; Yarkov, Roman S.; Mishchenko, Tatiana A.; Krut’, Victoria G.; Gavrish, Maria S.; Epifanova, Ekaterina A.; Babaev, Alexey A.; Vedunova, Maria V. (Frontiers in Cell and Developmental Biology, 2020)
Alzheimer’s disease (AD) is a widespread chronic neurodegenerative pathology characterized by synaptic dysfunction, partial neuronal death, cognitive decline and memory impairments. The major hallmarks of AD are extracellular senile amyloid plaques formed by various types of amyloid proteins (Aβ) and the formation and accumulation of intracellular neurofibrillary tangles. However, there is a lack of relevant experimental models for studying changes in neural network activity, the features of intercellular signaling or the effects of drugs on the functional activity of nervous cells during AD development. In this work, we examined two experimental models of amyloidopathy using primary hippocampal cultures. The first model involves the embryonic brains of 5ХFAD mice; the second uses chronic application of amyloid beta 1-42 (Aβ1-42). The model based on primary hippocampal cells obtained from 5xFAD mice demonstrated changes in spontaneous network calcium activity characterized by a decrease in the number of cells exhibiting Ca2+ activity, a decrease in the number of Ca2+ oscillations and an increase in the duration of Ca2+ events from day 21 of culture development in vitro. Chronic application of Aβ1-42 resulted in the rapid establishment of significant neurodegenerative changes in primary hippocampal cultures, leading to marked impairments in neural network calcium activity and increased cell death. Using this model and multielectrode arrays, we studied the influence of amyloidopathy on spontaneous bioelectrical neural network activity in primary hippocampal cultures. It was shown that chronic Aβ application decreased the number of network bursts and spikes in a burst. The spatial structure of neural networks was also disturbed that characterized by reduction in both the number of key network elements (hubs) and connections between network elements. Moreover, application of brain-derived neurotrophic factor (BDNF) recombinant protein and BDNF hyperexpression by an adeno-associated virus vector partially prevented these amyloidopathy-induced neurodegenerative phenomena. BDNF maintained cell viability and spontaneous bioelectrical and calcium network activity in primary hippocampal cultures.